« Écoutez mes chants d’universelle ivrognerie » : Alcools d’Apollinaire face au Dionysos nietzschéen - Camille Rodic (Carnets, 2021)
While inebriation is not a new theme in poetry, as is evidenced from the Greek dithyramb to Rimbaud’s “Bateau ivre”, the objective of this article is to demonstrate that the sources of inspiration for Alcools are not only poetic, but also philosophical. Without going so far as to pretend that Apollinaire, the poet with an Apollonian pseudonym and a work of Dionysian title, is a confirmed Nietzschean or even a poet-philosopher, the aim remains to study the effects of resonances between Alcools and the Nietzschean figure of Dionysus. Having explained the methodological justification for a comparison between Apollinaire and Nietzsche, we will discover different versions of inebriation (drunkenness, the relationship between inebriation and art, inebriation as an unconditional affirmation of life), before considering Orpheus as a figure of union between the Apollonian and the Dionysian.